Adaptive shaping of the behavioural and neuroendocrine phenotype during adolescence. Issue 1849 (22nd February 2017) - Zimmermann, Tobias D.; Kaiser, Sylvia; Hennessy, Michael B.; Sachser, Norbert
Abstract : Environmental conditions during early life can adaptively shape the phenotype for the prevailing environment. Recently, it has been suggested that adolescence represents an additional temporal window for adaptive developmental plasticity, though supporting evidence is scarce. Previous work has shown that male guinea pigs living in large mixed-sex colonies develop a low-aggressive phenotype as part of a queuing strategy that is adaptive for integrating into large unfamiliar colonies. By contrast, males living in pairs during adolescence become highly aggressive towards strangers. Here, we tested whether the high-aggressive phenotype is adaptive under conditions of low population density, namely when directly competing with a single opponent for access to females. For that purpose, we established groups of one pair-housed male (PM), one colony-housed male (CM) and two females. PMs directed more aggression towards the male competitor and more courtship and mating towards females than did CMs. In consequence, PMs attained the dominant position in most cases and sired significantly more offspring. Moreover, they showed distinctly higher testosterone concentrations and elevated cortisol levels, which probably promoted enhanced aggressiveness while mobilizing necessary energy. Taken together, our results provide the clearest evidence to date for adaptive shaping of the phenotype by environmental influences during adolescence.